2008
DOI: 10.1002/cncr.23437
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor receptor as a prognostic marker and a therapeutic target for imatinib mesylate therapy in osteosarcoma

Abstract: The purpose of this review was to determine whether imatinib mesylate (STI571, Gleevec) has a role in the treatment of osteosarcoma. The expression of plateletderived growth factor (PDGF) receptor and its ligand was examined in a panel of surgical specimens obtained from 54 osteosarcoma patients, and then the expression was compared with prognosis. The effects of imatinib mesylate on growth and molecular events in 10 patient-derived osteosarcoma cell cultures were investigated. Immunohistochemical studies demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 27 publications
7
79
1
Order By: Relevance
“…It is possible that novel therapeutic approaches may be necessary to improve the outcome of these patients. This might involve the combination of traditional cytotoxic agents with targeted therapies [16] and immunomodulatory agents [18]. Our second question was to determine prognostic factors for survival after local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that novel therapeutic approaches may be necessary to improve the outcome of these patients. This might involve the combination of traditional cytotoxic agents with targeted therapies [16] and immunomodulatory agents [18]. Our second question was to determine prognostic factors for survival after local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that the activation of MAPK by sertraline in hepatoma cells and fluoxetine in rat astrocytes has previously been reported (22,35). It should also be noted that in several osteosarcoma cell lines, imatinib was shown to reduce pAKT, while pMAPK remained constitutively activated (36). In a recent study it has been reported that the flavonoid, n arginine, inhibited vascular smooth muscle proliferation via the activation of the ERK signaling pathway (37).…”
Section: Discussionmentioning
confidence: 93%
“…34,35 Imatinib reduced the recruitment of myofibroblasts in mVEGF-164 transfectant transplants, most probably by interfering with signaling of the endogenous, stromal PDGF-B. However, the amount of pericyte-associated blood vessels and the epithelial structure were not altered in the imatinib-treated mVEGF-164 transfectant transplants.…”
Section: Discussionmentioning
confidence: 97%
“…PDGFR signaling was blocked with imatinib mesylate 34,35 (Glivec; Novartis Pharma, Basel, Switzerland) in nude mice either transplanted with a 1:1 mixture of HaCaT mVEGF-164 and HaCaT hPDGF-B transfectants or with HaCaT mVEGF-164 transfectants alone. Imatinib mesylate was given by oral gavage in 100 l of saline solution at a dose of 150 mg ϫ kg Ϫ1 body weight ϫ day…”
Section: Blockade Of Pdgfr Signaling In Vivomentioning
confidence: 99%